Data Privacy Studies (2010–2026): A Scopus-Based Bibliometric Analysis of Research Hotspots and Citation Dynamics - Loso Judijanto (West Science Information System and Technology, 2026)
The current study is designed to analyze the research on data privacy between the years 2010 and 2026 using bibliometrics. It seeks to explore collaboration trends, influential literature, and emerging research trends within the research area through co-authorship, citations, and co-keywords analysis. VOSViewer was used for the analysis, as well as visualization of co-citation and co-keyword networks, thus mapping out the intellectual and conceptual network of data privacy. As can be seen from the results, there have been many developments regarding the field under review, marked by increased international collaboration, especially among top-ranking countries such as China, the United Kingdom, India, and Germany. The citation network shows that the field relies not only on technologies like differential privacy and machine learning but also on behavior-based factors such as trust and privacy. The keyword network further indicates that "data privacy" plays an important role in this research domain, together with artificial intelligence, deep learning, and federated learning. The change in time for keywords implies a transition from traditional security methods to privacy-oriented techniques.